2021
DOI: 10.4149/neo_2021_210331n435
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model using hemoglobin, albumin, fibrinogen, and neutrophil-to-lymphocyte ratio to distinguish patients with colorectal cancer from those with benign adenoma

Abstract: Colorectal cancer (CRC) is associated with inflammation, activation of coagulation, and mild anemia. Hematological parameters reflecting ongoing cancer may have the potency to be effective for early diagnostics of CRC. The aim of this study was to examine the validity and relationship between some biochemical and hematological parameters for the early diagnosis of CRC. We designed a prospective observational cohort study to analyze whether these laboratory markers have the potency to distinguish benign tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the identification of CRC and colorectal adenoma patients, Roman et al [ 24 ] created a prediction model and nomogram using Hb, FIB, ALB, and NLR to predict the risk of CRC in patients, with an AUC value of 0.744. Another study showed that the diagnostic value of plateletcrit combined with CEA in the diagnosis of CRC was 0.835 (AUC), and the sensitivity was 0.700, while the specificity was 0.830 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the identification of CRC and colorectal adenoma patients, Roman et al [ 24 ] created a prediction model and nomogram using Hb, FIB, ALB, and NLR to predict the risk of CRC in patients, with an AUC value of 0.744. Another study showed that the diagnostic value of plateletcrit combined with CEA in the diagnosis of CRC was 0.835 (AUC), and the sensitivity was 0.700, while the specificity was 0.830 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ying et al demonstrated that brinogen-to-pre-albumin ratio (FPR) combined with CEA could effectively identify early-stage CRC from benign polyps, with an AUC, Sen, and Spe of 0.835, 68.30%, and 83.40 [9]. Furthermore, Roman et al showed that combining NLR and other blood parameters, such as HGB, FG and ALB, can distinguish CRC before planned surgery, and a predicted model based on above factors was created, whose AUC value was 0.744 [32]. In this study, multivariate logistic regression analysis reveled that high levels of age, maximum tumor size, WBC, and PCC score remained independent risk predictors.…”
Section: Discussionmentioning
confidence: 99%
“…When the body suffers from severe immune dysfunction and immunosuppression, it will cause a series of pathophysiological changes ( 18 ). LYM can specifically recognize and directly kill tumors or release a series of cytokines to activate anti-tumor immunity, which plays a key role in the production of cytokines that inhibit tumor proliferation and metastasis ( 19 ). NEU and LYM are objective indicators reflecting the inflammatory response and immune status of the body.…”
Section: Discussionmentioning
confidence: 99%